(untitled) (Medico Legal Update, 2021)
Background: One of the most prevalent chronic diseases isDiabetes mellitus that have adverse effect on the health, and the goal today being placed on disease prevention, controlling and screening. Aim: To assess knowledge,attitude and Practice of periodic screening of DM among teachers in Tikrit city. Subject and Method: The study is a cross-sectional study that had conducted from 1st of November 2018 until 30 of March 2019 on teachers in Tikrit city primary and secondary school using a questionnaire. Results: The knowledge regarding the diabetes and its screening a 24% were good and 46% were accepted regarding the disease symptoms and about its control 84% mention that diet modification is the best way then exercise and medication in lower percent while regarding complications 68% (much of them) knowledge were bad, About the importance of periodic screening the great percentage was yes. Conclusion: There was 93.3% who have knowledge about diabetes mellitus screening among school teachers. Teacher’s method for controlling diabetes mostly are diet modifications 84% then exercise 42.5%.